Renal Dysfunction is an Independent Risk Factor for Rebleeding After Endoscopic Hemostasis in Patients with Peptic Ulcer Bleeding - Ogiyama, Hideharu; Tsutsui, Shusaku; Murayama, Yoko; Matsushima, Kensuke; Maeda, Shingo; Satake, Shin; Seto, Kayo; Horiki, Masashi; Sanomura, Tamana; Imanaka, Kazuho; Iishi, Hiroyasu (Turkish Journal of Gastroenterology, 2021)
Background: Despite the progress in endoscopic hemostasis and pharmacological treatment, the mortality rate of peptic ulcer bleedingremains at 5–10%. Rebleeding after peptic ulcer bleeding is believed to be a risk factor for mortality. This study aimed to evaluatewhether renal dysfunction is a predictor of rebleeding after endoscopic hemostasis in patients with peptic ulcer bleeding.Methods: In this retrospective study, consecutive patients with peptic ulcer bleeding who underwent endoscopic hemostasis at ourHospital from January 2010 to December 2018 were enrolled. The relationship between rebleeding within 30 days after endoscopic hemostasisand the patients’ admission and endoscopic characteristics were analyzed using univariate and multivariate regression models.Results: Out of 274 patients with peptic ulcer bleeding, 17 (6.2%) patients experienced rebleeding. In the analysis of the patients’ admissioncharacteristics, estimated glomerular filtration rate (eGFR) < 30 mL/min/1.73 m2 was an independent risk factor for rebleeding(odds ratio 4.77, 95% confidence interval 1.168-18.211, p = 0.03). Patients with eGFR < 15 mL/min/1.73 m2 with or without hemodialysishad the highest rebleeding rate at 36.8%. With respect to endoscopic characteristics, the rate of rebleeding was associated with combinationtherapy (p < 0.0001) and active bleeding (p = 0.03).Conclusion: Renal dysfunction might be an independent risk factor for rebleeding after endoscopic hemostasis in patients with pepticulcer bleeding.